(3OQGSI JMdjdjI hebGQfI Hjf GdeGdjI GdYGeI aj UOhQ GdESdGe hGdeGdjI GdYGeI GdMOjKIs - (3GHQGgje GdbGSe(B, (3QMGMdIs ((3GdbGgQI(B:s (3ecJHI eOHhdj(B,s, 1999)
(3GdehGQO GdYGeI GdESdGejI(B- (3GdRcGI(B- (3GdZfGFe(B- (3GdeUQhaGJ GdYGeI GdESdGejI(B- (3ehba GdacQ GdESdGej ef eGdjI GdOhdI GdMOjKI(B.s
Keywords: (3GdEbJUGO GdESdGejs; (3GdeGdjI aj GdESdGes